Persistent Effects of Musical Training on Mathematical Skills of Children With Developmental Dyscalculia - Ribeiro, Fabiana Silva; Santos, Flávia Heloísa (Frontiers in Psychology, 2020)
Musical training (MT) is perceived as a multi-sensory program that simultaneously integrates visual, aural, oral, and kinaesthetic senses. Furthermore, MT stimulates cognitive functions in a ludic way instead of tapping straight into the traditional context of school learning. In this sense, MT might help children that thrive to handle mathematics. Nevertheless, the efficacy of MT over mathematics remains understudied, especially concerning longstanding effects. For this reason, this longitudinal study explored the effects of MT on numerical cognition and abstract visual reasoning using a double-blind and quasi-experimental design. We assessed two groups of children from primary schools, namely one with developmental dyscalculia [DD; n = 22] and another comprised typical development children [TD; n = 22], which concomitantly underwent MT at four different moments: Baseline (pre-MT assessment), mid-test (after seven weeks of MT), post-test (after 14 weeks of MT), and follow-up (10 weeks after the end of MT). Significant interactions were found between time and the groups for the numerical cognition systems, in which the DD group showed higher scores in number comprehension, number production at mid-test, and calculation at post-test compared to baseline. A key finding was that number production, number comprehension, calculation, and number line effects were time-resistant for the DD group since changes remained on follow-up. Moreover, no significant changes were found for abstract visual reasoning. In conclusion, the findings of our preliminary study showed that MT appears to be a useful tool for compensatory remediation of DD.